Linking theory with practice in the classroom : a hybrid model of lesson study research in action - Elliott, John, Dip. Phil. Ed.; Christoforatou, Vicky (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Focusing on the professional learning journeys of practicing teachers and their tutors, this book takes readers through the experiences of teachers on the Developing Innovative Pedagogies through the Lesson Study module at the University of East Anglia. Building on the perspectives of teachers practicing lesson study, the book delves into the design of a series of action research cycles to solve authentic learning and teaching problems in a variety of educational settings. In addition to theoretical tools and concepts on pedagogy, this book gives voice to teachers who become researchers while crossing the boundaries of school and university and the boundaries of theory and practice. The teacher researchers ask their own questions, test their hypotheses and work collaboratively with their school colleagues to experiment with teaching strategies aimed at learning with understanding. The chapters feature the voices of the pupils themselves and their experiences of learning within a range of educational settings and phases. Written for teachers, leaders in education, teacher educators and researchers, this book shows that the combination of good learning theories and teacher collaboration help bridge the gap between theory and practice in teachers' professional learning and enable learners to deepen their knowledge and understanding"--
Developing innovative approaches to teaching and learning through lesson study : a flexible course for teachers that integrates theory with practice in educational / settings / John Elliott -- Using the module to develop a school-wide approach to lesson study : the case of Litcham School / Rob Martlew -- Using lesson study to develop pupils' inference skills / Linda Timblin, John Cunningham and Christine Hinchliffe -- Improving extended writing : a lesson study / Josh Palmer and Tonya Bateman -- Developing communication skills in the early years : case study / Sarah Riley and Mary Newman -- Engagement and progress in the online classroom : learning narrative / Aimee Leggoe and Kate Finlay -- Developing critical thinking and collaborative skills in history through the use of technology / Adam Sayer -- Using lesson study to aid improvements in communication with employers in further education / Lauren Stroud -- Moving away from ticking off success criteria : how can grammatical techniques enrich writing? / Melissa Agnew -- Celebrating creativity and inclusion in art / Maria Grimmer -- The impact of the module on the professional development of participating teachers / John Elliott and Vicky Christoforatou -- Lesson study and the organizational culture of the school / Lucy Austin -- Implications for initial teacher education / Vicky Christoforatou, David Savage and Amanda Bell.
Keywords: Teachers -- In-service training -- Great Britain; Teachers -- Professional relationships -- Great Britain; Action research in education -- Great Britain; EDUCATION / Teaching Methods & Materials / General; EDUCATION / Research; EDUCATION / Higher